2011
DOI: 10.18552/joaw.v1i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Reader-Friendliness and Feedback: German-L1 Scholars’ Perceptions of Writing for Publication in English

Abstract: Failure to publish articles in the dominant Anglophone scientific journals has implications for multilingual scholars' future careers and for the global dissemination of scientific knowledge. Despite the importance of this topic, there have been few studies of the perceptions of multilingual scholars engaged in this process. In an effort to close this gap, an online questionnaire was emailed to 153 German-L1 scholars at the ETH Zurich, Switzerland. The 46 respondents ranked 'writing readerfriendly texts' as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…The research findings showed similar results to the study by Armstrong (2011) and Hyland and Hyland (2006) that an ability to produce L2 reader-friendly texts is the next challenge after English language competence for NNS scholars. A particular focus should be made on developing an NNS writer ability to differentiate between L1 and L2 research discourses and be aware of general research writing standards as well as of particular disciplinary similarities/differences in research texts.…”
Section: L1 Vs L2 Professional Writingsupporting
confidence: 85%
See 3 more Smart Citations
“…The research findings showed similar results to the study by Armstrong (2011) and Hyland and Hyland (2006) that an ability to produce L2 reader-friendly texts is the next challenge after English language competence for NNS scholars. A particular focus should be made on developing an NNS writer ability to differentiate between L1 and L2 research discourses and be aware of general research writing standards as well as of particular disciplinary similarities/differences in research texts.…”
Section: L1 Vs L2 Professional Writingsupporting
confidence: 85%
“…L2 professional writing researchers also fail to apply different forms of L2 feedback though it is a key prerequisite which encourages and facilitates the process of writing (Hyland & Hyland, 2006;Armstrong, 2011). Finally, the interview results reveal that the writers are not always aware of and are not able to effectively use key resources for L2 high quality writing.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…These records draw on empirical data from surveys and interviews to investigate the researchers' personal experiences in writing journal articles and taxonomize the journal reviewers' comments on language shortcomings in manuscripts written in English by scholars with L1s other than English. It is argued that linguistic difficulties involve lack of clarity and reader-friendliness, paucity of expression in English, subsequent language reuse at both lexical and syntactic levels, and problems in handling the discourse pragmatics and in constructing an authorial identity (Armstrong, 2011;Buckingham, 2014;Chiu, 2001;Flowerdew & Li, 2007;Ouellette, 2008;Shi, 2012). Concern about language-related burdens is not unsupportive, one might further say, of arguments deployed on behalf of linguistic diversity.…”
Section: The Dominance Of English: Linguistic Accommodation and Asymmmentioning
confidence: 99%